Study of orchid resistance induced by Ceratorhiza sp. against ORSV infection based on peroxidase activity - Anggi Anggreiny; Tundjung Tripeni Handayani; Mahfut Mahfut (UNIVERSITAS NEGERI PADANG, 2021)
Orchid is one of the popular ornamental plants that widely grown in Indonesia. However, the process of orchid cultivation is often hampered by virus infections. The virus that often infects the orchids is Odontoglossum ringspot virus. Viruses that enter orchid cells and replicate will activate the orchid’s defense response. This defense response is characterized by the increase of peroxidase activity. The peroxidase enzyme works in the formation of lignin to thicken cell walls and prevent viruses from entering other cells. In addition, the orchid defense response can also be activated through induced systemic resistance by inoculation of Ceratorhiza sp. as endophytic mycorrhizae. In this study, Factorial Complete Randomized Design (CRD) was used with 2 factors. Factor 1 is the type of orchid (Phalaenopsis amabilis and Dendrobium discolor) and factor 2 is the type of treatment (inoculation of mycorrhizae, virus, and mycorrhizae-virus). The orchid’s resistance level is determined by the analysis results of peroxidase activity using spectrophotometer. The results obtained indicate that all treatment combinations strongly influence the increase of peroxidase activity. Peroxidase activity of Phalaenopsis amabilis is 1.42 [(Umg) / min] and Dendrobium discolor is 1.64 [(Umg) / min] in average. Peroxidase activity on Dendrobium discolor was higher than on Phalaenopsis amabilis. This indicates that Dendrobium discolor has a higher level of resistance when compared to Phalaenopsis amabilis.Proses budidaya anggrek seringkali terkendala oleh infeksi virus. Adapun virus yang paling banyak menginfeksi anggrek adalah ORSV. Virus yang masuk ke dalam sel anggrek dan bereplikasi akan mengaktifkan respon pertahanan anggrek. Respon pertahanan ini ditandai dengan peningkatan aktivitas peroksidase. Respon pertahanan anggrek juga dapat diaktifkan melalui induksi resistensi sistemik dengan inokulasi Ceratorhiza sp. sebagai mikoriza endofit. Dalam penelitian ini digunakan Rancangan Acak Lengkap (RAL) Faktorial dengan 2 faktor. Faktor pertama adalah jenis anggrek (Phalaenopsis amabilis dan Dendrobium discolor) dan faktor kedua adalah jenis perlakuan (inokulasi mikoriza, virus, dan mikoriza virus). Tingkat ketahanan anggrek ditentukan dari hasil analisis aktivitas peroksidase menggunakan spektrofotometer. Hasil yang diperoleh menunjukkan bahwa semua kombinasi perlakuan sangat berpengaruh terhadap peningkatan aktivitas peroksidase. Aktivitas peroksidase Phalaenopsis amabilis rata-rata 1,42 [(U/mg)/ menit] dan Dendrobium discolor 1,64 [(U/mg)/ menit]. Aktivitas peroksidase pada Dendrobium discolor lebih tinggi dibandingkan dengan Phalaenopsis amabilis. Hal ini menunjukkan bahwa Dendrobium discolor memiliki tingkat ketahanan yang lebih tinggi jika dibandingkan dengan Phalaenopsis amabilis.